1994
DOI: 10.1002/eji.1830240338
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania major‐specific CD8+ T cells are inducers and targets of nitric oxide produced by parasitized macrophages

Abstract: Lines of Leishmania major-specific CD8+ T cells were derived from the lymph nodes and spleens of CBA mice, immune following resolution of a primary infection, 7 days after secondary challenge with viable L. major. Specific stimulation of these CD8+ T cells by bone marrow-derived macrophages infected with L. major led to the release of interferon-gamma by CD8+ T cells and nitric oxide by macrophages. Interestingly, the nitric oxide released by bone marrow-derived macrophages down-regulated the production of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 41 publications
3
37
0
1
Order By: Relevance
“…This observation is in agreement with the specialized capacity of DC to present exogenous antigens to CD8 ϩ T cells (13,34). Prior studies using infected macrophages to activate CD8 ϩ T cells in each case used primed CD8 ϩ T cells (7,20,40), suggesting that whereas DC may be necessary to prime naïve CD8 ϩ T cells, infected macrophages can present MHC class I-restricted epitopes to trigger cytokine release from CD8 ϩ effector T cells and thus be activated for killing. We confirmed these observations by showing that at a high MOI, infected Mø can present NT-OVA to primed OT-I T cells, though 20-fold-less efficiently than DC.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This observation is in agreement with the specialized capacity of DC to present exogenous antigens to CD8 ϩ T cells (13,34). Prior studies using infected macrophages to activate CD8 ϩ T cells in each case used primed CD8 ϩ T cells (7,20,40), suggesting that whereas DC may be necessary to prime naïve CD8 ϩ T cells, infected macrophages can present MHC class I-restricted epitopes to trigger cytokine release from CD8 ϩ effector T cells and thus be activated for killing. We confirmed these observations by showing that at a high MOI, infected Mø can present NT-OVA to primed OT-I T cells, though 20-fold-less efficiently than DC.…”
Section: Discussionsupporting
confidence: 82%
“…In each case, however, the concentration of NT-OVA available for processing following uptake of heat-killed parasites or parasites expressing nonsecreted NT-OVA will be low compared to NT-OVA actively secreted by live parasites that can accumulate within the vacuole and enter the phagosome-associated MHC class I-restricted presentation pathway (1,18,19). Previous work using poorly defined antigens (e.g., live parasites or whole cellular extracts) suggested that secreted and cell surface-associated Leishmania antigen, but not nonsecreted antigens, were presented by APC to CD8 ϩ T cells (7,16,20,23,40) and CD4…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to leishmaniasis has been associated with a predominant IL-12 and IFN-␥ production from the Ag-specific CD4 ϩ Th lymphocyte population termed as Th1 immune response (61,62). These cells along with CD8 ϩ T cytotoxic lymphocytes are then effective in promoting macrophage activation, and the intracellular Leishmania are killed in a NO-dependent manner (63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Natural killer cells may be a very important source of IFN-␥ in this situation. While previous reports have shown that CD8 ϩ T cells may not be essential for primary immunity (17), there have been several studies which have shown that CD8 ϩ T cells do have a role in secondary responses (24,25,34). LACK DNA induces antigen-specific CD8…”
Section: Discussionmentioning
confidence: 99%